2010
DOI: 10.1002/stc.428
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response attenuation of structures using shape memory alloy dampers

Abstract: Smart materials such as shape memory alloys (SMAs) are recently being used in earthquake engineering applications to control the response of structures. In this paper, a shape-memory alloy damper device made up of austenite wires (e.g. Nickel Titanium wires) is used as a passive energy absorber. NiTi wires are very attractive for passive vibration control as they have a pseudo-elastic property and can sustain large amounts (upto 10% strain) of inelastic deformation. Moreover, in contrast to regular metallic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…Shape memory alloys (SMA) have attracted attention as a smart material that can be employed in civil structures to dissipate seismic energy and provide self-centering capabilities. Among various applications of SMAs in seismic engineering, [5][6][7][8][9][10] SMA-based bracing systems have been one of the most commonly studied approach to enhance seismic performance of civil structures. Several researchers have numerically investigated the performance of SMA-braced frames by assuming an SMA brace that consists of short SMA elements and connected to a rigid segment.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory alloys (SMA) have attracted attention as a smart material that can be employed in civil structures to dissipate seismic energy and provide self-centering capabilities. Among various applications of SMAs in seismic engineering, [5][6][7][8][9][10] SMA-based bracing systems have been one of the most commonly studied approach to enhance seismic performance of civil structures. Several researchers have numerically investigated the performance of SMA-braced frames by assuming an SMA brace that consists of short SMA elements and connected to a rigid segment.…”
Section: Introductionmentioning
confidence: 99%
“…NiTi shape memory alloys (SMAs) are unique functional materials that have the ability to undergo large deformations and can return to their original state through removal of stress (known as the superelastic effect) and dissipate energy without residual deformation . With the advantageous properties of pseudoelasticity, large ductility, large elastic strain (6–8%), excellent corrosion resistance, re‐centering, and fatigue resistance, many researchers have used SMAs for the vibration control of civil structures and have verified their effectiveness in seismic‐resistant designs and applications …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SMA wire dampers could effectively reduce the seismic response. Parulekar et al proposed an SMA damper device and conducted cyclic testing on the device to prove its effectiveness in energy absorption capacity. Li et al experimentally studied two SMA dampers installed in the first story of a 1/4‐scale five‐story two‐bay frame and observed the effective response‐mitigation performance of the SMA dampers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out in the field of response, optimization and design of structures equipped with passive dampers . Xia and Hanson studied two 10‐story frame structures with ADAS devices with different parameters to find out their performance under seismic loading.…”
Section: Introductionmentioning
confidence: 99%